1993
DOI: 10.1111/j.1600-0447.1993.tb03376.x
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of paroxetine and placebo in depressed outpatients

Abstract: To compare the safety and efficacy of paroxetine (n = 167) and placebo (n = 169), data from 4 centres using the same protocol were pooled. A double-blind parallel group design was used, with therapy lasting 6 weeks. Significant differences between paroxetine- and placebo-treated patients were found on the major efficacy outcome variables by week 2 and on all efficacy variables by week 4 of the study. Improvement on the sleep factor of the Hamilton Rating Scale for Depression was found after 7 d. Observer and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

1994
1994
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(22 citation statements)
references
References 14 publications
(8 reference statements)
0
22
0
Order By: Relevance
“…Numerous clinical trials have assessed the effi cacy of antidepressants, generally indicating that antidepressant treatment of major depression is superior to placebo treatment (Dunbar et al 1993;Ellingrod and Perry 1995;Ballenger 1996;Croft et al 1999;Feighner and Overo 1999;Gorman 1999). The majority of studies that compare multiple antidepressants including SSRIs and tricyclic antidepressants (TCAs) show no signifi cant effi cacy differences between them (Holliday and Plosker 1993;Bennie et al 1995;Patris et al 1996;Sechter et al 1999;Stahl 2000;Kroenke et al 2001), but with very high sample size or with meta-analysis using data from multiple studies, TCAs and dual reuptake inhibitors show greater effi cacy than SSRIs (Thase 2002).…”
Section: Approaches To Mdd Treatmentmentioning
confidence: 99%
“…Numerous clinical trials have assessed the effi cacy of antidepressants, generally indicating that antidepressant treatment of major depression is superior to placebo treatment (Dunbar et al 1993;Ellingrod and Perry 1995;Ballenger 1996;Croft et al 1999;Feighner and Overo 1999;Gorman 1999). The majority of studies that compare multiple antidepressants including SSRIs and tricyclic antidepressants (TCAs) show no signifi cant effi cacy differences between them (Holliday and Plosker 1993;Bennie et al 1995;Patris et al 1996;Sechter et al 1999;Stahl 2000;Kroenke et al 2001), but with very high sample size or with meta-analysis using data from multiple studies, TCAs and dual reuptake inhibitors show greater effi cacy than SSRIs (Thase 2002).…”
Section: Approaches To Mdd Treatmentmentioning
confidence: 99%
“…It has a low side-effect profile, even at high doses. 1 Altough transient mild elevations of liver enzymes have been observed with use of paroxetine, 11,12 severe hepatoxicity is a rare condition and only ten cases were reported in the literature. Hepatotoxicity can be hepatocellular, cholestatic or mixed type.…”
Section: Discussionmentioning
confidence: 99%
“…Functional measures: In accord with the renewed interest in "remission", i.e., the virtual absence of symptoms and restoration of social function, as an outcome index, as against response ( Ͼ 50% reduction in baseline symptomatology), recent evidence shows a place for measures of social functioning and quality of life Healy 1998;Bosc et al 1997). Studies have shown such measures to be sensitive to drug actions when symptom severity in itself was not (Dunbar et al 1991). Signs of social impairment in outpatient depressives can be subtle.…”
Section: Conceptions Of Depression and The Mechanisms Of Drug Actionmentioning
confidence: 99%